Could personality, characteristics of violations, and perceptions of the organizational environment be a factor driving the whistleblowing intention? - Hastuti, Theresia Dwi; Indarto, Stefani Lily; Claudia, Gita (Business: Theory and Practice, 2023)
The objective of this paper is to examine the effect of personality, perceptions of the organizational environment, and characteristics of violations on the whistleblowing intention in educational institutions. This study is expected to contribute to the management of higher education to protect their organization from fraud. Personality variable has three proxies, namely perceptions of reporting costs, locus of control, and organizational commitment. The organizational environment perception has 3 proxies, namely the perception of the internal control system, organizational climate and organizational support, while the characteristics of fraud are proxied by the status of the violation and the seriousness of the violation. The participants of this study were lecturers in universities in Semarang. The data were collected from the surveys using random sampling method. Questionnaires on whistleblowing were distributed to lecturers and we get 100 participants. The data was processed use a multiple linear regression with SPSS software. The result of this study showed that the organizational climate and the seriousness of the violation positively affected the whistleblowing intention. Meanwhile, the organizational commitment, perception of the cost of violations, internal locus of control, organizational support, the internal control system and the status of the violation did not significantly affect the whistleblowing intention.